Measuring Evangelicals: Practical Considerations for Social Scientists-CORRIGENDUM - Burge, Ryan P. (Politics and religion, 2018)
Evangelicals garner much attention in polling and public opinion research, yet measuring white evangelicals remains elusive, even opaque. This paper provides practical guidance to researchers who want to measure or analyze evangelicals. In the social sciences,many have adopted a detailed religious affiliation approach that categorizes evangelicals based on the religious tradition of the denominations to which they belong. Others have used a simpler self-identification scheme, which asks respondents if they consider themselves born-again or evangelical. While the affiliation ands elf-identification schemes are predominant, a practical examination of these approaches has been absent. Using several waves of the General Social Survey and the Cooperative Congressional Election Study, we compare them. We find almost no statistical differences between the two measurements in prominent demographic, political, or religious factors. Thus, we suggest that for most a simple question about broad religious affiliation followed by a born-again or evangelical self-identification question will suffice.